Prospective Mathematics Teachers’ Perceptions of the Use of Problem-Based Learning (PBL) Models in Mathematics Learning - Nurdalilah Nurdalilah; Ariyadi Wijaya; Elly Arliani (MASI Mandiri Edukasi, 2026)
This study examines prospective mathematics teachers’ perceptions of Problem-Based Learning (PBL) in mathematics education, focusing on their understanding of PBL characteristics, the role of problems as learning triggers, and their readiness to implement PBL in future teaching practice. The study addresses the gap between positive perceptions of PBL and pedagogical readiness for inquiry-based mathematics instruction. A mixed-methods approach with a sequential explanatory design was employed. Quantitative data were collected through questionnaires administered to 35 prospective mathematics teachers, while qualitative data were obtained through semi-structured interviews to deepen the interpretation of the quantitative findings. The results indicate that prospective teachers generally hold highly positive perceptions toward PBL, particularly regarding its ability to support critical thinking, collaboration, conceptual understanding, and contextual mathematics learning. Qualitative findings revealed that participants viewed problems in PBL as starting points for conceptual exploration rather than exercises given after instruction. However, participants also identified challenges related to authentic problem design, classroom management, inquiry facilitation, and time allocation. The study highlights the importance of strengthening experiential PBL training, problem design, and facilitation skills in mathematics teacher education programs. Although the limited sample size restricts generalizability, the study contributes to understanding the relationship between perceptions and pedagogical readiness in PBL implementation.